Ismail Gasprinski’s Influence on Turkestan Jadidism and Modern Muslim Identity - Ismailova Tozagul Qahramon qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Ismail Gasprinski stands as a pivotal figure in understanding the development of Turkestan Jadidism and its lasting impact on modern Muslim identity. His efforts to reform education and promote cultural awareness in the late 19th and early 20th centuries sparked a transformative movement among Turkic Muslims. By emphasizing the importance of modern education, he sought to equip individuals with the tools necessary to navigate a rapidly changing world. This endeavor aligns with broader historical trends, such as the evolution of Jadid studies, which has examined the educational and political ramifications of this movement since Uzbekistans independence in 1991 (ABDIRASHIDOV Z). Additionally, the complexities surrounding the identity formation of Muslims in Turkestan during this period underscore the necessity of analyzing Gasprinski’s role, as such examinations reveal the significant shifts in socio-political dynamics that influenced contemporary Muslim identity (Gadzhiev J, 2017). Thus, understanding his contributions is essential to grasping the broader narrative of Jadidism and its implications today.